Nanoparticle-Mediated Cell Capture Enables Rapid Endothelialization of a Novel Bare Metal Stent - Tefft, Brandon J; Uthamaraj, Susheil; Harbuzariu, Adriana; Harburn, J Jonathan; Witt, Tyra A; Newman, Brant; Psaltis, Peter J; Hlinomaz, Ota; Holmes, David R; Gulati, Rajiv; Simari, Robert D; Dragomir-Daescu, Dan; et al. (Tissue engineering. Part A, 2018)
Incomplete endothelialization of intracoronary stents has been associated with stent thrombosis and recurrent symptoms, whereas prolonged use of dual antiplatelet therapy increases bleeding-related adverse events. Facilitated endothelialization has the potential to improve clinical outcomes in patients who are unable to tolerate dual antiplatelet therapy. The objective of this study was to demonstrate the feasibility of magnetic cell capture to rapidly endothelialize intracoronary stents in a large animal model. A novel stent was developed from a magnetizable duplex stainless steel (2205 SS). Polylactic-co-glycolic acid and magnetite (Fe3O4) were used to synthesize biodegradable superparamagnetic iron oxide nanoparticles, and these were used to label autologous blood outgrowth endothelial cells. Magnetic 2205 SS and nonmagnetic 316L SS control stents were implanted in the coronary arteries of pigs (n = 11), followed by intracoronary delivery of magnetically labeled cells to 2205 SS stents. In this study, we show extensive endothelialization of magnetic 2205 SS stents (median 98.4% cell coverage) within 3 days, whereas the control 316L SS stents exhibited significantly less coverage (median 48.9% cell coverage, p < 0.0001). This demonstrates the ability of intracoronary delivery of magnetic nanoparticle labeled autologous endothelial cells to improve endothelialization of magnetized coronary stents within 3 days of implantation.
Keywords: prasata; Swine; fenotyp; Phenotype; Endothelial Cells; endoteliální buňky; cell-targeting; Nanoparticles; Stainless Steel; nanotechnology; nanočástice; Stents; magnetic stent; Animals; kovy; ženské pohlaví; zvířata; endothelialization; stenty; Metals; nerezavějící ocel; Female